Self-Similar Automorphisms of a Free Group of Countable Rank - Tomaszewski, Witold (MATHEMATICA SCANDINAVICA, 2015)
We investigate self-similar automorphisms of a free group $F$ of infinite countable rank, that is automorphisms for which their actions on $F$ and $F^{′}$ are similar. We show properties, examples and counterexamples of self-similar automorphisms and study the subgroup generated by self-similar automorphisms.